2010
DOI: 10.1016/j.hrthm.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac and extracardiac markers of inflammation during atrial fibrillation

Abstract: BACKGROUND-A decrease in inflammation after cure of atrial arrhythmias suggests that such arrhythmias are pro-inflammatory, and lower inflammatory marker levels in the coronary sinus suggest that atrial arrhythmias result in the intracardiac appropriation of inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 27 publications
3
87
1
4
Order By: Relevance
“…It is noteworthy that one of these studies (negative for an association) had enrolled a cohort, 45% of which had diabetes, cardiac failure, and/or myocardial infarction as comorbidities, all known to be associated with inflammation (Kimmel et al, 2013), while the other two (one negative and one weakly positive for the association) included no information on comorbidities. Furthermore, and perhaps more crucially significant, there is a well-documented relationship between atrial fibrillation, the major indication for use of warfarin and other vitamin K antagonists in these studies, and raised inflammatory biomarkers, especially IL-6 (Henningsen et al, 2009;Marcus et al, 2010;Celebi et al, 2011;Smit et al, 2012;Wu et al, 2013). Inevitably, a question arises concerning the extent to which the CYP2C9 genotype of the cohorts of these three studies was predictive of their CYP2C9 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that one of these studies (negative for an association) had enrolled a cohort, 45% of which had diabetes, cardiac failure, and/or myocardial infarction as comorbidities, all known to be associated with inflammation (Kimmel et al, 2013), while the other two (one negative and one weakly positive for the association) included no information on comorbidities. Furthermore, and perhaps more crucially significant, there is a well-documented relationship between atrial fibrillation, the major indication for use of warfarin and other vitamin K antagonists in these studies, and raised inflammatory biomarkers, especially IL-6 (Henningsen et al, 2009;Marcus et al, 2010;Celebi et al, 2011;Smit et al, 2012;Wu et al, 2013). Inevitably, a question arises concerning the extent to which the CYP2C9 genotype of the cohorts of these three studies was predictive of their CYP2C9 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial fat has been linked with increased expression of local inflammatory markers, particularly in the LA, which may play a role in AF genesis (41,42). A recent study showed lower success rates after non-hybrid AF ablation in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…146,487-489 Baseline CRP levels have been associated with the risk of recurrent AF after catheter ablation. 278 Recently, colchicine has been used to prevent atrial fibrillation recurrence after PV isolation. 490 It is also possible that AF in itself can result in inflammation and the development of an 'atrial myocarditis'.…”
Section: Role Of Myocarditismentioning
confidence: 99%